2005
DOI: 10.1542/peds.2005-0300
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Household Firearms and Firearm-Storage Practices in the 50 States and the District of Columbia: Findings From the Behavioral Risk Factor Surveillance System, 2002

Abstract: ABSTRACT. Objectives. To examine the prevalence of household firearms and firearm-storage practices in the 50 states and the District of Columbia and estimate the number of children exposed to unsafe storage practices.Methods. We analyzed data from the 2002 cross-sectional Behavioral Risk Factor Surveillance System survey of 240 735 adults from randomly selected households with telephones in the 50 states and the District of Columbia.Results. Nationally, 32.6% of adults reported that firearms were kept in or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 34 publications
5
58
0
Order By: Relevance
“…38 Prevalence of gun ownership by household varies significantly geographically, with an estimated low of 5.2% in the District of Columbia to 62.8% of all households in Wyoming. 39 In a study of gun-owning Americans with children under 18 years of age, 21.7% stored a gun loaded, 31.5% stored a gun unlocked, and 8.3% stored at least 1 gun unlocked and loaded. 40 Household firearm owners with adolescents 13 through 17 years of age report leaving their firearms unlocked 41.7% of the time, compared with only 28.8% of household firearm owners with children 0 through 12 years of age.…”
Section: Guns and Gun Ownershipmentioning
confidence: 99%
“…38 Prevalence of gun ownership by household varies significantly geographically, with an estimated low of 5.2% in the District of Columbia to 62.8% of all households in Wyoming. 39 In a study of gun-owning Americans with children under 18 years of age, 21.7% stored a gun loaded, 31.5% stored a gun unlocked, and 8.3% stored at least 1 gun unlocked and loaded. 40 Household firearm owners with adolescents 13 through 17 years of age report leaving their firearms unlocked 41.7% of the time, compared with only 28.8% of household firearm owners with children 0 through 12 years of age.…”
Section: Guns and Gun Ownershipmentioning
confidence: 99%
“…Furthermore, the potential for state policies to be a product of the selectivity of the residents of the state complicates disentangling the effects of state-level firearm laws. 11 Lawmakers in states with a high proportion of firearm owners may be more reluctant to pass laws that regulate firearm practices; consequently, observed correlations between laws and state-level firearm ownership may reflect state population characteristics or state "gun culture" to a greater extent than states' firearm policy (or lack thereof). In line with the American Academy of Pediatrics' recommendation that parents who own firearms store them locked and unloaded, with ammunition locked and stored separately, 12 we examined how laws aimed at firearm storage practices-along with general state-level firearm laws-are associated with firearm ownership and storage behaviors among families with preschool-aged children.…”
mentioning
confidence: 99%
“…4,6,8,[12][13][14][15][17][18][19][20] A 2002 national study reported that in households with children Ͻ18 years old, 5.5% had loaded household firearms and 2.5% had firearms that were both loaded and unlocked. 21 The American Academy of Family Physicians recommends firearm education for families in homes with weapons and supports legislation that requires firearms to be stored locked and unloaded. 22 The American Academy of Pediatrics (AAP) recommends that guns be removed from the home if possible, or, at the very least, stored safely (locked and unloaded).…”
mentioning
confidence: 99%